2011
DOI: 10.3324/haematol.2011.052829
|View full text |Cite
|
Sign up to set email alerts
|

CD69 is independently prognostic in chronic lymphocytic leukemia: a comprehensive clinical and biological profiling study

Abstract: BackgroundCD69 is expressed in several hemopoietic cells and is an early activation marker in chronic lymphocytic leukemia. Chronic lymphocytic leukemia is a clinically heterogeneous disease which needs novel prognostic parameters which can be easily and efficiently managed. Design and MethodsWe investigated CD69 by flow cytometry in a series of 417 patients affected by chronic lymphocytic leukemia and compared this to other biological and clinical prognosticators. ResultsCD69 was associated with Rai stages (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
(44 reference statements)
2
29
0
Order By: Relevance
“…45 Moreover CLL patients had significantly higher numbers of proliferating CD4 + and CD8 + T cells, which was more evident at disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…45 Moreover CLL patients had significantly higher numbers of proliferating CD4 + and CD8 + T cells, which was more evident at disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…CD29 and CD49d together form the VLA-4 protein; CD49d is known to empower CLL cells to migrate into lymphoid tissue. 36,37 CD69, an early activation marker in CLL correlating with a poor prognosis, 38 was heterogeneously expressed in MCL and B-PLL. Altogether, the genes found to be differentially expressed among CLL, MCL, and B-PLL are in line with data reported for CLL and MCL in literature and thereby confirm the suitability of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from others, this unsupervised procedure did not consider any clinical parameter to set the cut-off, obviating selection bias. 8,9,12 Interestingly, LAIR1 expression was related to the occurrence of autoimmune phenomena. Both a direct antiglobulin test and autoimmune hemolytic anemia were more frequently observed in LAIR1 -patients, with a quite high percentage of LAIR1 -patients having autoimmune hemolytic anemia (7.2%) at presentation with CLL.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Del Poeta et al recently reported a reduced prognostic power of CD49d when all significant prognostic factors for CLL were included in the multivariate analysis. 12 The cut-off for positivity of LAIR1 was set at 30%. This choice of cut-off was made considering the distribution of frequencies of positive cells in our cohort of patients, as previously done by Damle et al for CD38 4 (Online Supplementary Methods and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation